Energy, Transportation, Air Quality, Climate Change, Health Nexus: Sustainable Energy is Good for Our Health - Erickson, Larry E.; Jennings, M. (My University, 2016)
The Paris Agreement on Climate Change has the potential to improve air quality and human health by encouraging the electrification of transportation and a transition from coal to sustainable energy. There will be human health benefits from reducing combustion emissions in all parts of the world. Solar powered charging infrastructure for electric vehicles adds renewable energy to generate electricity, shaded parking, and a needed charging infrastructure for electric vehicles that will reduce range anxiety. The costs of wind power, solar panels, and batteries are falling because of technological progress, magnitude of commercial activity, production experience, and competition associated with new trillion dollar markets. These energy and transportation transitions can have a very positive impact on health. The energy, transportation, air quality, climate change, health nexus may benefit from additional progress in developing solar powered charging infrastructure.
Citation: Erickson, L. E., & Jennings, M. (2017). Energy, Transportation, Air Quality, Climate Change, Health Nexus: Sustainable Energy is Good for Our Health. Aims Public Health, 4(1), 47-61. doi:10.3934/publichealth.2017.1.47
Keywords: Sustainability; Solar; Electric Vehicles; Shade; Infrastructure; Parking